2014
DOI: 10.3109/17453674.2013.878829
|View full text |Cite
|
Sign up to set email alerts
|

Can total knee arthroplasty be safely performed in patients with chronic renal disease?

Abstract: Background and purposeThe prevalence of chronic renal disease (CRD) is rising worldwide. Patients with CRD are more likely to have associated medical problems and are at greater risk of postoperative morbidity and mortality. We evaluated patient characteristics and risk of early revision, surgical site infection (SSI), thromboembolic events, mortality, and re-admission of patients with CRD undergoing total knee arthroplasty (TKA). We hypothesized that this patient population would have higher rates of complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 25 publications
(37 reference statements)
1
43
0
1
Order By: Relevance
“…Recent studies have shown the prevalence of chronic kidney disease in an elective arthroplasty setting to be between 6% and 27% of patients [5,9,18]. Bozic et al [7,19] have previously shown that renal disease is an independent risk factor for early revision after primary hip and knee arthroplasty, as well as periprosthetic joint infection.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent studies have shown the prevalence of chronic kidney disease in an elective arthroplasty setting to be between 6% and 27% of patients [5,9,18]. Bozic et al [7,19] have previously shown that renal disease is an independent risk factor for early revision after primary hip and knee arthroplasty, as well as periprosthetic joint infection.…”
Section: Discussionmentioning
confidence: 97%
“…In a comparatively small cohort of 526 patients, Ackland et al [5] found that patients with CKD had increased pulmonary, infectious, and cardiovascular complications while experiencing an increased length of stay of 4 days. Miric et al [9,18] found an increased risk for 90-day readmission for both THA and TKA patients in the setting of CRD. Pugely et al [10] corroborated these findings, showing that dialysis, high serum BUN, and elevated serum creatinine were predictive risk factors for 30-day readmission.…”
Section: Discussionmentioning
confidence: 98%
“…Chronic kidney disease is common in adults older than 65 years, who are the fastest growing subset of patients with end-stage renal disease. 23 While studies have shown that THA and TKA can be performed safely in this patient cohort, 24,25 close attention must be paid to mitigate the perioperative risks associated with chronic renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective review of 142 patients with CKD (stages 3 through 5) undergoing elective primary and revision THA and total knee arthroplasty (TKA), Ackland et al 24 reported a twofold risk of pulmonary, infectious, cardiovascular, gastrointestinal, wound, renal, neurologic, and pain complications compared with that of normal patients. 27 In contrast, retrospective cohort studies have shown that arthroplasty may be well tolerated, with mortality and complication rates that are comparable to those in the general population. Smaller and more dated retrospective studies have demonstrated complication rates of up to 100%.…”
Section: Outcomes Of Elective Orthopaedic Proceduresmentioning
confidence: 99%